Ontology and revelation in Bavinck's Stone Lectures - Shannon, Nathan D. (Scottish journal of theology, 2020)
This essay examines Herman Bavinck's Stone Lectures (1908), published as Philosophy of Revelation, for indications of a noteworthy conception of the relation between ontology and revelation. One discovers in the lectures that in responding constructively to various challenges to the Christian faith, Bavinck pushes in a direction documented in recent studies of his work: toward doctrinal organicism. What emerges in terms of ontology and revelation is Bavinck's belief that Christianity is distinguished primarily by confession of a real divine relational initiative, understood in terms of the incarnation, which serves as the ontological precondition of divine revelation and thus as vindication of creaturely naming of God.